A Study on Robotics in Contemporary Ecosphere - Dr. V.Vinodhini; Navi Narmadha .J; M.Sneha; G.Ashwin (International Journal of Engineering and Management Research, 2023)
This paper presents an ongoing study investigating the impact of robotics in the contemporary world, the robotics in education has gained an increased attention over the last decades. Using robots as a vehicle to interest pupils and young children in science and technology and in addition to improve their technical and social skills and in medical health as a service robot has become a widespread approach in various countries World Wide. Nowadays by transferring knowledge from large, diverse, modern ML models can solve specific downstream tasks either zero-shot or with small task-specific datasets to a high or large level of performance. At the same time as this capability of robotics has been enrolled in other fields such as computer vision, natural language processing or speech recognition, where the overview capabilities of the models are particularly demanding due to the difficulty collection of modern world robotic data.